2021
DOI: 10.1055/s-0040-1722313
|View full text |Cite
|
Sign up to set email alerts
|

All-Inside PCL Reconstruction

Abstract: Many different techniques with multiple graft types have been described for the reconstruction of the injured posterior cruciate ligament (PCL); autograft versus allograft, single- versus double-bundle, open inlay versus arthroscopic inlay versus arthroscopic transtibial, and recently described the arthroscopic “all-inside” socket technique. Reported clinical outcomes have demonstrated no significant difference in any of these PCL reconstruction techniques, likely because of the heterogeneity in injury charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…After receiving institutional review board approval, we identified consecutive patients who underwent a primary PCLR using the all-inside technique 9 , 27 , 30 , 40 from October 2012 to January 2019. Over the study period, all surgeries were performed by fellowship-trained orthopaedic surgeons (M.J.S.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After receiving institutional review board approval, we identified consecutive patients who underwent a primary PCLR using the all-inside technique 9 , 27 , 30 , 40 from October 2012 to January 2019. Over the study period, all surgeries were performed by fellowship-trained orthopaedic surgeons (M.J.S.…”
Section: Methodsmentioning
confidence: 99%
“…The preferred technique of the surgeons was all-inside PCLR using a quadrupled peroneus longus or tibialis anterior tendon allograft with both tibial and femoral suspensory fixation. 40 A quadruple looped allograft with a final length of approximately 90 mm with a final diameter between 10 and 12 mm was used for all reconstructions. A 40-mm tibial socket was drilled using the anatomic PCL Tibial Guide (Arthrex) and the FlipCutter II (Arthrex).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This area, the "no-safe zone", makes some knee surgeons less confident and willing to perform this surgical procedure [3][4][5]. Surgical reconstruction of the PCL can be performed using two main techniques: the tibial tunnel or the tibial inlay technique [6,7]. The tibial tunnel technique approaches the PCL tibial insertion using a specific guide under arthroscopic control and, in some circumstances, fluoroscopic control.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Persistent posterior laxity has been the most commonly reported complication of PCLR with single-bundle and isometric techniques associated with the highest incidences. [26][27][28][29] Based on reported advantages and disadvantages, we have employed two tibial fixation techniques, transtibial (TT) 4,30 with an all-soft tissue graft [30][31][32] and tibial inlay (TI) with a bone block 33,34 , for anatomic double-bundle PCLRs. Selection of TT versus TI has been primarily governed by the presence of additional injuries to the knee, previous attempts at PCLR, and the patient's body mass index (BMI).…”
Section: Introductionmentioning
confidence: 99%